Anarchist Geographers and Feminism in Late 19th Century France: the Contributions of Elisée and Elie Reclus. - Ferretti, Federico (Historical Geography, 2016)
Women were part of the political and scientific networks that contributed to Elisée Reclus’ enterprise of the New Universal Geography and built the “Antiauthoritarian International,” although they have been generally neglected by historiography. During the French Second Empire (1852-1870), Elie and Elisée Reclus collaborated with some of the most famous French militant women and feminists, like Louise Michel, Léodile Champseix (known under the masculine pseudonym of André Léo) and Noémi Reclus, including creating and participating in a league for women’s rights. This paper aims to clarify the working of these networks and their specific intersections with geography in the period of the 1871 Paris Commune and in the following ten years of exile, mainly through an analysis of correspondence by Louise Michel, Léodile Champseix and the members (male and female) of the Reclus family. My main hypothesis is that the collaboration between feminist militants and anarchist geographers, questioning patriarchy, endorsing ‘free union’ and mixed education, anticipated several features of successive anarchist feminisms, and that its study can be a useful contribution to a “Feminist Historical Geography.”